La identificación de los tópicos y los focos - Gutiérrez Bravo, Rodrigo (El Colegio de México, 2008)
This paper is an overview article of a number of word order phenomena related to information structure. Specifically, this paper addresses the issue of the determination of a laguage´s unmarked word order and the perturbations form this order that result from topicalization and focusing. Illustrative data is presented from both European and Amerindian languages in order to make a crosslinguistic comparison of the phenomena under consideration. The description of topic and focus presented here relates not only to their syntax but also discusses their basic intonational and prosodic properties.